Factors Associated With Experiences of Harassment or Abuse Among Lesbian, Gay, Bisexual, Trans, Queer, and Asexual Young People With Disability in Australia - Amos, Natalie (Journal of interpersonal violence, 2024)
Lesbian, gay, bisexual, trans, queer, and asexual (LGBTQA+) young people with disability are known to experience higher rates of harassment or abuse than LGBTQA+ young people without disability. This study focused on participants in Australia and identified factors associated with harassment or abuse among LGBTQA+ adolescents and young adults who reported a disability as well as associations with mental health outcomes. Analyses were conducted from a national survey that included 2,500 LGBTQA+ people who reported a disability and were aged 14 to 21 years. Measures included experiences in the past 12 months of verbal and physical harassment or abuse due to one’s sexual orientation or gender identity, sexual harassment or abuse, mental health, suicidality, and sociodemographic traits. Overall, 48.4% of participants with disability reported experiencing verbal harassment or abuse, 12.4% physical harassment or abuse, and 29.7% sexual assault or harassment. In multivariable regression analyses, verbal harassment or abuse was significantly more likely among trans men, participants with an intellectual disability, and those who were “out” to most or all of their family. Physical harassment or abuse was significantly more likely among participants with a physical or sensory disability. Sexual harassment or abuse was significantly more likely among trans women and participants with a physical or sensory disability. Participants who experienced harassment or abuse were also significantly more likely to have attempted suicide in the past 12 months. These findings will assist policymakers and practitioners in identifying contexts linked to a heightened risk of abuse among LGBTQA+ young people with disability and further underscore an immediate need to address and prevent harm in this population.